2020
DOI: 10.1177/0306624x20904695
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Parental Incarceration on Psychopathy, Crime, and Prison Violence in Women

Abstract: There is a growing interest in understanding the consequences of parental incarceration. Unfortunately, research exploring the long-term criminological and personality effects in female offspring is limited, particularly among second-generation female offenders. In a sample of 170 female offenders, we first assessed the correlations between psychopathy facets, prison violence, and types of crime. Next, we tested the association between childhood exposure to paternal and/or maternal incarceration on ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 70 publications
(105 reference statements)
1
10
0
Order By: Relevance
“…Evidence of this association remained significant even when PI exposure was experienced during different developmental periods. While the studies in this review overwhelmingly identified this association, four studies did not detect a statistically significant relationship between PI and drug use (Murray, Loeber, et al, 2012; Phillips et al, 2002; Quinn et al, 2016; Thomson et al, 2020).…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Evidence of this association remained significant even when PI exposure was experienced during different developmental periods. While the studies in this review overwhelmingly identified this association, four studies did not detect a statistically significant relationship between PI and drug use (Murray, Loeber, et al, 2012; Phillips et al, 2002; Quinn et al, 2016; Thomson et al, 2020).…”
Section: Resultsmentioning
confidence: 74%
“…Kopak and Smith‐Ruiz (2016) reported that African‐American children in their study who experienced MI, especially, fared worst on a range of drug‐related outcomes, including marijuana‐ and cocaine‐related problems such as giving up or cutting down on activities that might interfere with drug use, including getting together with friends or relatives, going to work or school or participating in sports. While Thomson acknowledged that girls in their study who experienced PI (MI in particular) were negatively impacted by this exposure, they reported that PI (including maternal, paternal or both parents incarcerated) was not significantly associated with the commission of a drug‐related crime (Thomson et al, 2020). While PI exposure increased the odds of receiving a drug use disorder diagnosis according to Gifford's study, adolescents with parents who had been incarcerated did not have significantly higher rates of marijuana abuse or dependency or other drug use or dependency in another (Gifford et al, 2019).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The affective facet is characterized by callousness, lack of empathy, and a lack of remorse ( Sellbom, 2011 ). The behavioral facet measures boredom susceptibility and unstable, angry, impulsive attitudes and behaviors ( Garofalo et al, 2019 ; Thomson et al, 2020a ). Research has demonstrated that the interpersonal facet is related to low agreeableness and higher levels of narcissism and moral disengagement ( Garofalo et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…12 Having any parent incarcerated during childhood can be a risk factor for psychopathy for their children. 13 The study officially reported that violent misconduct in prison independently contributed to psychopathy and impulsivity, 14 and having adequate social support is protective against psychopathy. 15 A considerable portion (37-93%) of the effects of childhood maltreatment was the risk for psychopathic personality traits.…”
Section: Introductionmentioning
confidence: 99%